Effect of CMC concentration and Storage Time on the Quality of Fruit Sorbet - Faradisa Puteri; Rona J. Nainggolan; Lasma Nora Limbong (Universitas Sumatera Utara, 2015)
The study was conducted to determine the effect of the concentration of CMC and storage time on the quality of fruit sorbet . This research was performed by using a completely randomized design with two factors,i.e.: the concentration of CMC (C) : (0,25% , 0 ,50% , 0,75% and 1% ) and storage time ( L ) : (0 days , 5 days , 10 days , 15 days and 20 days ) . The parameters analyzed were the levels of vitamin C (mg/100g), total acid (%), total dissolved solids (oBrix), melting time (minutes/50g) , organoleptic value of color, aroma, flavor and texture. The results showed that the concentration of CMC gave highly significant effect on levels of vitamin C, total acid, melting time, total dissolved solids, the value of organoleptic color, aroma, flavor, and texture. The duration of storage gave highly significant effect on the levels of vitamin C, total acid, melting time. Concentration CMC of 1% and 15 days storage time gave the best quality of fruit sorbet and more acceptable. Keywords : Fruit sorbet, soursop, dragon fruit, coconut water, carboxy methyl cellulose.